Production and marketing of gated communities in Istanbul - Tüzin Baycan-Levent; Aliye Ahu Gülümser (European Regional Science Association (ERSA), 2004)
Gated communities are part of the trend of suburbanization that is based on the creation of self-contained, separate communities with carefully constructed identities. There are many definitions of gated communities and they differ from country to country. However, a general definition can be given as “physical privatized areas where outsiders and insiders exist”. In parallel to the increasing diversity and multiplicity, gated communities have grown in both developed and developing countries and they have radically transformed the urban environment. For residents, gated communities are lifestyles choices. For developers, they can be a marketing angle, another way to target specific submarkets or a necessity to meet demand in some areas. The aim of this paper is to investigate the phenomenon of “gated communities” which is one of the most important driving forces in housing market. The paper will focus on the production and marketing of gated communities in Istanbul. How is the production and marketing process of gated communities? The paper will provide an answer to this question while evaluating the data obtained from the extensive survey questionnaires filled out by developers of gated communities.
Keywords: 330